2018
DOI: 10.26710/jafee.v4i2.526
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Financial Literacy and Parental Socialization on the Saving Behavior of University Level Students

Abstract: This is an explanatory study on the impact of financial literacy and parental socialization on the saving behavior of university level students. Using primary data collection method, 400 questionnaires were distributed to the students of universities across Pakistan. Pearson correlation and multiple regression analysis are employed by using SPSS. Our results demonstrate that financial literacy and parental socialization positively influence the saving behavior of students. Our result revealed that the students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 24 publications
1
15
0
2
Order By: Relevance
“…Financial literacy refers to understanding the main financial terms and concepts needed in managing daily life (Brigham & Houston, 2014). As explained by Afsar et al (2018), financial literacy is a skill that can help individuals make effective financial decisions. Alwi et al (2015) revealed that parental socialization increases children's financial literacy.…”
Section: Theoretical Framework and Empirical Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Financial literacy refers to understanding the main financial terms and concepts needed in managing daily life (Brigham & Houston, 2014). As explained by Afsar et al (2018), financial literacy is a skill that can help individuals make effective financial decisions. Alwi et al (2015) revealed that parental socialization increases children's financial literacy.…”
Section: Theoretical Framework and Empirical Studiesmentioning
confidence: 99%
“…Alwi et al (2015) revealed that parental socialization increases children's financial literacy. According to Afsar et al (2018) discussions between parents and children about financial problems affect saving and borrowing habits. Homan (2016) argues that parental socialization can help increase individuals' savings and reduce their borrowing.…”
Section: Theoretical Framework and Empirical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Parents role has been categorized in two ways, some parents do not allow children to be involved in decision, as parents take all decisions, and other category of parents, are interactive in nature, they try to teach their children regarding financial matters (Ribeiro, Fonseca, & Soares 2018). Similarly, Afsar, Chaudhary, Iqbal, and Aamir (2018) also found that, parents with interactive characteristics also positively associated with saving. Robertson-Rose (2020) also identified dual nature of parents related to financial matters which can have both positive as well as negative effects on savings.…”
Section: Family Background and Savingmentioning
confidence: 99%
“…Financial literacy is a major construct in finance, business as and a social construct and has many important implications. As a financial construct, financial literacy helps individuals manage spending and savings (Afsar, Chaudhary, Iqbal, & Aamir, 2018;Ali, Rahman, & Bakar, 2015;Mahdzan & Tabiani, 2013;Xiao & Porto, 2017), plan retirement (Agnew, Bateman, & Thorp, 2013;Boisclair, Lusardi, & Michaud, 2017;Brown & Graf, 2013;Crossan, Feslier, & Hurnard, 2011;Klapper & Panos, 2011;Lusardi & Mitchell, 2007, 2011Sekita, 2011;, plan investments (Almenberg & Dreber, 2015;Jariwala, 2013;Van Rooij, Lusardi, & Alessie, 2011), make household decisions, and increase wealth or returns on wealth (Behrman, Mitchell, Soo, & Bravo, 2012;Grohmann & Schoofs 2021;Jappelli & Padula, 2013). As a social construct, it reduces stress, illness, financial disputes, abuse of children, and conflicts among families (Fox, Bartholomae, & Lee, 2005).…”
Section: Introductionmentioning
confidence: 99%